Inference for misclassified multinomial data with covariates. Issue 4 (16th June 2020) - Wang, Shijia; Wang, Liangliang; Swartz, Tim B.
Abstract : This article considers multinomial data subject to misclassification in the presence of covariates which affect both the misclassification probabilities and the true classification probabilities. A subset of the data may be subject to a secondary measurement according to an infallible classifier. Computations are carried out in a Bayesian setting where it is seen that the prior has an important role in driving the inference. In addition, a new and less problematic definition of nonidentifiability is introduced and is referred to as hierarchical nonidentifiability. Résumé : Les auteurs considèrent des données multinomiales sujettes à une mauvaise classification en présence de covariables affectant à la fois les probabilités de bonne et de mauvaise classification. Un sous‐ensemble des données peut faire l'objet d'une seconde mesure par un classificateur infaillible. Les auteurs développent leurs calculs dans un cadre bayésien où la loi a priori joue un rôle important pour l'inférence. Les auteurs présentent également une nouvelle définition moins problématique de la non‐identifiabilité, soit la non‐identifiabilité hiérarchique.